2014
DOI: 10.4315/0362-028x.jfp-13-386
|View full text |Cite
|
Sign up to set email alerts
|

Impact of High Hydrostatic Pressure Treatment on Microbial Communities in Chinese Water-Boiled Salted Duck

Abstract: The objective of this study was to determine the impact of high hydrostatic pressure (HHP) treatment on microbial communities in Chinese water-boiled salted duck (CWBSD) and the synergistic effect of HHP and mild heat treatment. In this work, the bacterial diversity was evaluated by using both a culture-dependent method and denaturing gradient gel electrophoresis. The total aerobic bacterial counts in pressure-treated samples were significantly lower than those in controls, which indicated that HHP could exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…For the inactivation of microorganism in WBSDM treated by HHP, Shen and others () studied the effect of HHP combined with heat on the shelf‐life and the total number of bacterial colonies. Feng and others () determined the impact of HHP treatment on microbial communities in WBSDM, and confirmed that B. cereus and S. warneri became the dominant bacteria in products after treatment. Therefore, in this study, temperature played an important role in pressure inactivation of pressure‐resistant bacteria in WBSDM.…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations
“…For the inactivation of microorganism in WBSDM treated by HHP, Shen and others () studied the effect of HHP combined with heat on the shelf‐life and the total number of bacterial colonies. Feng and others () determined the impact of HHP treatment on microbial communities in WBSDM, and confirmed that B. cereus and S. warneri became the dominant bacteria in products after treatment. Therefore, in this study, temperature played an important role in pressure inactivation of pressure‐resistant bacteria in WBSDM.…”
Section: Resultsmentioning
confidence: 85%
“…WBSDM is a highly popular meat product in China, and there is a demand to develop methods to extend its shelf‐life without affecting its quality. Previous studies have shown that HPP treatment can be used to inactivate most microorganisms in WBSDM, except for B. cereus and S. warneri (Feng and others ). Therefore, the optimal treatment of the high pressure combined with moderate heat to inactivate the pressure‐resistant bacteria in WBSDM has been studied here, and any impact on meat quality attributes after the suitable treatment has been determined.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations